Theoretical and methodological approaches to activism during the COVID-19 pandemic— between continuity and change - Coen, Sharon; Vezzoli, Michela; Zogmaister, Cristina (Frontiers in Political Science, 2022)
In order to understand the way in which scholars approach the study of activism at a time of crisis, a scoping review was conducted to identify the extant empirical work on activism during the COVID-19 crisis. Our search resulted in 23 published papers across disciplines. Results showed elements of continuity and change in scholars' theoretical and empirical approaches to new and old forms of activism emerging at this time of crisis. In general, we found that COVID-19 led to the employment of novel and adaptive approaches from both the activists and the researchers, who tactically modified their strategies in light of the new demands. We conclude by suggesting that incorporating an analysis of the tools of protest, combined with an analysis of the adaptive strategies adopted by communities at a time of crisis might further our understanding of the ontology—as well as the epistemology—of social movements. Moreover, the study highlighted existing tensions between academia and other social stakeholders, which deserve further exploration.